“Saving Lives, Protecting Livelihoods, and Safeguarding Nature”: Risk-Based Wildlife Trade Policy for Sustainable Development Outcomes Post-COVID-19 - Booth, Hollie; Arias, Melissa; Brittain, Stephanie; Challender, Daniel W. S.; Khanyari, Munib; Kuiper, Timothy; Li, Yuhan; Olmedo, Alegria; Oyanedel, Rodrigo; Pienkowski, Thomas; Milner-Gulland, E. J. (Frontiers in Ecology and Evolution, 2021)
The COVID‐19 pandemic has caused huge loss of life, and immense social and economic harm. Wildlife trade has become central to discourse on COVID-19, zoonotic pandemics, and related policy responses, which must focus on “saving lives, protecting livelihoods, and safeguarding nature”. Proposed policy responses have included extreme measures such as banning all use and trade of wildlife, or blanket measures for entire Classes. However, different trades pose varying degrees of risk for zoonotic pandemics, while some trades also play critical roles in delivering other key aspects of sustainable development, particularly related to poverty and hunger alleviation, decent work, responsible consumption and production, and life on land and below water. Here we describe how wildlife trade contributes to the UN Sustainable Development Goals (SDGs) in diverse ways, with synergies and trade-offs within and between the SDGs. In doing so, we show that prohibitions could result in severe trade-offs against some SDGs, with limited benefits for public health via pandemic prevention. This complexity necessitates context-specific policies, with multi-sector decision-making that goes beyond simple top-down solutions. We encourage decision-makers to adopt a risk-based approach to wildlife trade policy post-COVID-19, with policies formulated via participatory, evidence-based approaches, which explicitly acknowledge uncertainty, complexity, and conflicting values across different components of the SDGs. This should help to ensure that future use and trade of wildlife is safe, environmentally-sustainable and socially-just.